Public Relations Dalam Pelayanan Prima Di Kantor Kecamatan Galesong Utara Kabupaten Takalar - Awalia, Sitti Nazmia; Usman, Jaelan; Yahya, Muhammad (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
This study purposed to find out how Public Relations in superfine service at the North Galesong District Office, Takalar Regency. The method was descriptive qualitative. Data analysis techniques used  data reduction, data exposure and conclusion making then  data was collected through observation, interviews, and documentation. The results of this study showed that Public relations at the North Galesong  District office could  be seen from community service that had helped the community to meet their needs according to their fields. In maintaining good relations, public relations was  good, it had provived a good services by using language that was easy to understand. Public relations morals and behavior in providing services had implemented well, smiles and greetings, but there were still employees who had  not shown good morals and behavior to the community. Keywords: public relations, service, public